Improving the Methodological Framework for Statistical Accounting of Environmental Protection Expenditure in the Context of Renewable Energy Sources - Т. KOBYLYNSKA; O. MOTUZKA; N. PARFENTSEVA (Naukovij Vìsnik Nacìonalʹnoï Akademìï Statistiki, Oblìku ta Auditu, 2019)
The article is devoted to improvements of the methodological framework for statistical accounting of environmental protection expenditure in Ukraine in the context of renewable energy sources (wind and solar energy). It is argued that any study focused on accounting of environmental protection expenditure or development of renewable energy sources needs computations and analyses of indicators based on statistical data. Problems of improvements in statistical accounting are, therefore, have critical significance for such studies. The important objective is related with improvements of statistical accounting of the capacities generating energy from alternative sources and costs on their installation and modernization, which will enable to compare data all the levels, reveal main tendencies, patterns and changes, assess indicators and take sound decisions on environmental protection.